2020
DOI: 10.1080/09168451.2020.1809989
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the bacterial community structures on human hair and scalp

Abstract: In this study, we investigated and compared characteristics of the bacterial community structures on hair (scalp hair) and scalp in 18 individuals. Significant differences were found between the sites, in terms of cell density, alpha and beta diversity, and relative abundance of the phyla, Firmicutes and Proteobacteria, whereas no difference was found in relative abundance of the phylum Actinobacteria. Bacteria of the genus Cutibacterium showed similar relative abundance at both sites, whereas those of genus P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Thirdly, we confirmed that the average bacterial cell number per cm 2 of scalp hair shaft was stable at approximately 3.5 (± 7.6) × 10 5 by estimating the 16S rRNA gene copy number (Table 2 ), which was consistent with that obtained in previous studies 16 , 17 , 22 . These results suggest that scalp hair shafts have a load of 10 5 bacterial cells without exception, and that shampooing or chemical treatment of scalp hair shaft would not significantly affect the total cell number (Table 4 ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Thirdly, we confirmed that the average bacterial cell number per cm 2 of scalp hair shaft was stable at approximately 3.5 (± 7.6) × 10 5 by estimating the 16S rRNA gene copy number (Table 2 ), which was consistent with that obtained in previous studies 16 , 17 , 22 . These results suggest that scalp hair shafts have a load of 10 5 bacterial cells without exception, and that shampooing or chemical treatment of scalp hair shaft would not significantly affect the total cell number (Table 4 ).…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies of the human microbiome on scalp hair have shown that bacterial community structure varies between individuals and is distinguishable from that of other human skin microbiomes 14 17 . This study provided the first insights into the factors that contribute to the formation of bacterial community structures on scalp hair shaft.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations